1991
DOI: 10.1177/096032719101000108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Exposure to Aluminium and Ethanol on Aluminium Body Burden and some Neuronal, Hepatic and Haematopoietic Biochemical Variables in the Rat

Abstract: The effects of the daily administration of aluminium (25 mg kg-1, orally), ethanol (10% v/v, in drinking water) or both to adult rats, for 6 weeks, on the amount of aluminium present in the tissues and the functioning of brain biogenic amines, hepatic and serum transaminases and some haematopoietic variables were investigated. Ethanol alone was seen to inhibit the activity of δ-aminolevulinic acid dehydratase (ALAD), while aluminium alone elevated the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 20 publications
0
6
2
Order By: Relevance
“…It has been observed that combined exposure of aluminium and ethanol produced a more pronounced inhibition of hepatic alanine aminotransferase activity than either aluminium or ethanol alone (9). However, in the present investigation, ALT activity remained unaltered.…”
Section: Ethanol and Biochemical Changes Of Braincontrasting
confidence: 71%
See 3 more Smart Citations
“…It has been observed that combined exposure of aluminium and ethanol produced a more pronounced inhibition of hepatic alanine aminotransferase activity than either aluminium or ethanol alone (9). However, in the present investigation, ALT activity remained unaltered.…”
Section: Ethanol and Biochemical Changes Of Braincontrasting
confidence: 71%
“…This study suggested that, the ethanol exposure facilitate the aluminum accumulation in brain. Flora et al (9) Groups exposed to different treatment Normal Aluminum Ethanol Al & EtOH micro moles/100mg wet tissue aluminium and ethanol than in those exposed to aluminium alone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As with lead, simultaneous exposure to aluminium and ethanol also deplete brain dopamine (DA) and 5-hydroxytryptamine (5-HT) levels, when compared to rats given aluminium alone (Flora et al, 1991). Also, the concentration of aluminium in the blood and liver was significantly higher in rats exposed to both aluminium and ethanol than in those exposed only to aluminium.…”
Section: Environmental Neurotoxicants and Ethanol Intakementioning
confidence: 99%